PARADIGMA PENDIDIKAN ISLAM DALAM MASYARAKAT JAWA - Jupriyanto Jupriyanto (LPPM Institut Agama Islam Al-Hikmah Tuban, 2011)
Islamic Education in the Java community through multiple ways including the adaptation of the teachings of Islam with Javanese culture. The adaptation are: (1) adaptation in the field of Fiqh. Characteristics of the Java community is more steady and confident when any conduct of worship using the Arabic pronunciation coupled with the Java language, this is done by the Java community until now as a result of Islamic education in Java, for example by combining the teachings of fiqh in the Java language when reciting intention in taking a ritual ablution,